If You Build It, They Will Come - Courtney Hoffner (Issues in Science and Technology Librarianship)
Opportunities for the UCLA Science Librarians to connect with new graduate students have dwindled over the years. After struggling to be included in department orientation sessions, we decided to create an orientation fair of our own, now one of our most successful outreach events to connect with new students.